2006
DOI: 10.1021/tx050237e
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Geldanamycin and C17-Substituted Analogues with Glutathione:  Product Identifications and Pharmacological Implications

Abstract: 17-Dimethylaminoethylamino-17-demethoxygeldanamycin (DMAG) and 17-allylamino-17-demethoxygeldanamycin (17-AAG) are two derivatives of geldanamycin (GA) that are currently undergoing clinical evaluation as anticancer agents. These agents bind to heat shock protein 90 (hsp90), resulting in the destabilization of client proteins and inhibition of tumor growth. In a search for the mechanism of hepatotoxicity, which is a dose-limiting toxicity for these agents, we found that GA and its derivatives, 17-AAG and 17-DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 25 publications
3
77
1
Order By: Relevance
“…First, GA and 17-AAG were recently shown to bind GSH in a nonenzymatic reaction in vitro (42). Direct binding of 17-AAG to GSH may reduce binding to Hsp90 in vivo and could therefore explain protection of tumor cells by increased GSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…First, GA and 17-AAG were recently shown to bind GSH in a nonenzymatic reaction in vitro (42). Direct binding of 17-AAG to GSH may reduce binding to Hsp90 in vivo and could therefore explain protection of tumor cells by increased GSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…This conjugation with sulfur-containing nucleophiles may contribute to the dose-limiting hepatotoxicity of these quinone-containing compounds. 13,14 For these reasons, new non-quinone 1 analogs with improved pharmacological profiles are needed. 15,16 Recently, we reported the development of non-quinone 1 analogs by a mutasynthetic approach and directed biosynthetic method.…”
mentioning
confidence: 99%
“…16 13 C NMR and HMQC spectra revealed the presence of 28 carbon signals comprising two carbonyl, six aromatic or olefinic quaternary, six aromatic or olefinic methine, four oxymethine, two aliphatic methine, two aliphatic methylene, two O-methyl, and four C-methyl carbons. Additionally, four exchangeable proton signals were observed in DMSO-d 6 : two hydroxyl protons (d 5.10 and 4.76), one phenolic hydroxyl proton (d 9.13) and one amide proton (d 9.33).…”
mentioning
confidence: 99%
“…It has been reported that an Nglycyltransferase is discovered in S. sannanensis IFO 14239 (sannamycin-producer), and the gene sequences of similar glycyltransferase have been detected in other aminoglycoside antibiotic producers by DNA hybridization [30]. Up to now, there has been no report that the biological modification of GDM analogues at C-19, although this position can be nonenzymatically modified by glutathione [31]. GDMCT-1-1 was not observed in the wild-type S. hygroscopicus 17997 strain, because its intermediate product (GDMCT-1-7, a possible substrate of the putative glycyltransferase) is rapidly carbamoylated by GdmN, and therefore is not available for latter glycylation reaction.…”
Section: Discussionmentioning
confidence: 99%